Effectiveness of Biologics, Patient-Reported Outcomes, and Clinical Photography in a Subset of Patients with Moderate-to-Severe Psoriasis: Week 12 Results from the Psoriasis Study of Health Outcomes (PSoHO) - Travaglini M; Maul JT; Kors C; Zaheri S; Gerwien J; Müller M; Brnabic A; Sabatino S; Schuster C; Tsai TF (Dove Medical Press, 2023)
Massimo Travaglini,1 Julia-Tatjana Maul,2,3 Christian Kors,4 Shirin Zaheri,5 Jens Gerwien,6 Michaela Müller,6 Alan Brnabic,6 Silvia Sabatino,6 Christopher Schuster,6,7 Tsen-Fang Tsai8 1Centre for the Treatment of Psoriasis, Di Summa-Perrino Hospital, Brindisi, Italy; 2Department of Dermatology and Venereology, University Hospital of Zurich, Zurich, Switzerland; 3Faculty of Medicine, University of Zurich, Zurich, Switzerland; 4Private Practice Dermatology, Berlin, Germany; 5Department of Dermatology, The Harley Street Clinic, HCA Healthcare UK, London, UK; 6Eli Lilly and Company, Indianapolis, IN, USA; 7Department of Dermatology, Medical University of Vienna, Vienna, Austria; 8Department of Dermatology, National Taiwan University Hospital and National Taiwan University College of Medicine, Taipei City, TaiwanCorrespondence: Tsen-Fang Tsai, Department of Dermatology, National Taiwan University Hospital and National Taiwan University College of Medicine, 7, Chung-Shan South Road, Taipei City, 100225, Taiwan, Tel +886 223123456#65734, Email tftsai@yahoo.comPurpose: Since skin is highly accessible, clinical photography is a useful tool to visually substantiate the real-world effectiveness outcomes of biologic-treated adults with moderate-to-severe psoriasis (PsO). We report the effectiveness and patient-reported outcomes at Week 12 between anti-interleukin (IL)-17A biologics and other biologics as well as ixekizumab and guselkumab in patients with available clinical photography at baseline and Week 12.Patients and Methods: The Psoriasis Study of Health Outcomes (PSoHO) is an international, non-interventional, cohort study investigating the effectiveness of biologics in adults with moderate-to-severe psoriasis at Week 12. Outcomes included the proportion of patients who achieved 90% improvement in Psoriasis Area and Severity Index (PASI90) and/or static Physician Global Assessment (sPGA) 0/1 (primary endpoint), PASI100, PASI90, Dermatology Life Quality Index (DLQI), and Itch Numeric Rating Scale (NRS) (secondary endpoints) at Week 12. Data are reported descriptively.Results: This analysis included 59 biologic-treated (23 anti-IL-17A; 36 other biologics) patients with available clinical photographs from the overall PSoHO study (n=1981). At baseline, the mean (standard deviation [SD]) age was 45.7 (11.1) years, 71.2% were male, 52.5% were bio-experienced and the median (interquartile range) duration of disease was 10.5 (12.4) years. Mean (SD) PASI was 16.9 (9.3) and sPGA was 3.5 (0.8). At Week 12, 65.2%/47.2% of the anti-IL-17A/other biologics cohort achieved the primary outcome. Response rates for PASI90/100 were numerically higher with anti-IL-17A than with other biologics. Patients receiving anti-IL-17A had numerically better outcomes for DLQI 0/1 and Itch NRS than those receiving other biologics at Week 12. Clinical photographs confirmed skin improvements in ixekizumab- and guselkumab-treated patients.Conclusion: This subgroup analysis showed that anti-IL-17A biologics are effective at rapidly improving signs and symptoms of PsO and improving quality of life. Additionally, serial photography provided visual evidence of biologic treatment response over time.Keywords: psoriasis, ixekizumab, guselkumab, real-world, clinical photography